ChemInform Abstract: Expedient Base‐Mediated Desulfitative Dimethylamination, Oxidation, or Etherification of 2‐(Methylsulfanyl)‐3, 5‐dihydro‐4H‐imidazol‐4‐one Scaffolds. Issue 6 (11th February 2014) - Khan, Shahnawaz; Tyagi, Vikas; Mahar, Rohit; Bajpai, Vikas; Kumar, Brijesh; Chauhan, Prem M. S.
Abstract The desulfitative dimethylamination of imidazolones (I) is achieved with DMF under optimized microwave conditions.